Sistem Pembayaran Kontrak kerja pembuatan Pagar Panel Beton (Studi Pada PG Kebon Agung Malang) - Arif Wahyudi (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
This research was conducted to analyze the work contract payment system in the manufacture of concrete panel fences at PG Kebon Agung Malang so that it can provide information in the form of relevant data, have timeliness, are accurate and useful for the wearer. The qualitative approach used in this research is based on primary data by obtaining data directly from resource persons and using secondary data whose data sources are documents, notes, and other supporting data. The results of this study explain the accounting information system in the form of a system flow chart that explains how the flow of the work contract payment system in making concrete panel fences at Kebon Agung PG starts from CV offering a tender, after being determined the tender winner, the user gives a tender winner letter so that the CV is the winner of the tender. can start his work. After the work is 92.5% completed, CV makes a report of completion of work as evidence that CV has completed part of its project and submits payment by including invoices, receipts, tax invoices, minutes, and SPK to the user to get a blank cash payment request for the first term . Payment of terms for bothparties CV makes a retention report (retention) as the completion of the 7.5% work submitted to the user along with a work agreement letter and a letter of completion of SP work.